PERANCANGAN PROSES INTEGRASI SISTEM INFORMASI AKADEMIK (SIAKAD) DAN SISTEM PEMBELAJARAN DARING (SPADA) MENGGUNAKAN METODE OOAD (OBJECT ORIENTED ANALYSIS AND DESIGN) - Puspaningrum, Hamnah; Indra Gita Anugrah; Widyasari Puspa Permata Witra (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
Universitas Muhammadiyah Gresik (UMG) uses two main information systems to support academic and learning processes, namely the Academic Information System (SIAKAD) and the Online Learning System (SPADA). These two systems have not been integrated, causing inefficiencies in managing academic data such as attendance, assessment, and management of learning materials. This research aims to design integration between SIAKAD and SPADA using Object-Oriented Analysis and Design (OOAD) method with bottom-up approach. The OOAD method was chosen because of its ability to model the system in a structured and object-oriented manner without changing the main structure of the system that is already running, through the Unified Modeling Language (UML) diagram. The results showed that the integration of the two systems can improve the efficiency of academic data management, reduce the risk of data errors, and facilitate the administration and learning process for lecturers, students, and administrative staff. In addition, this integration is expected to reduce duplicate processes and facilitate users by providing a centralized system.